GE_GERICHTE A/2379/2021 vom 15. November 2021 - GE Cour de justice (2021)
RETRAIT DE PERMIS;SIGNALISATION ROUTIÈRE;SIGNAL LUMINEUX;FAUTE GRAVE;ACCIDENT | LCR.16c.al2.leta; LCR.15c.al1.leta; LCR.27.al1